CONCEPT OF REGULATIONS FOR ACCESS OF PRIVATE LOCOMOTIVES TO PUBLIC RAILWAY INFRASTRUCTURE - V. I. Matsiuk (Nauka ta progres transportu, 2020)
Purpose. Scientific research is aimed at gaining new knowledge about the structure of a typical regulatory and technological document (regulation) of access for private-owned train locomotives to public railway infrastructure. Methodology. To obtain relevant empirical data, the authors performed a review of previous studies on the topic of work using full-text and abstract databases. In accordance with the principles of system analysis and mathematical logic, structural-logical models of the order of interaction between the units of the operator (owner) of the public railway infrastructure and representatives of the owner of private locomotives have been developed. Findings. The authors proved: 1) the regulation of access of private train locomotives to public infrastructure is a certain procedure (technological process) for the interaction of the owner (operator) of private locomotives with the units of the owner of the infrastructure (dispatch or operational personnel, employees of commercial and carriage facilities); 2) the structure of the typical regulation includes the following blocks: the technological process, the procedure for processing transportation documents and charging fees, the procedure for operating private locomotives and preparing of locomotive’s foot-plate staff for the tour; the procedure and responsibility of the parties in case of emergency situations. Originality lies in improving the models for the organization of railway carriage traffic volumes and the movement of trains on public railways, which, unlike the existing ones, imply the decentralized management of the locomotive fleet. Practical value lies in the possibility of direct practical application of the proposed models for the creation of standard recommendations for drawing up rules for the access of private locomotives to the hauling operations on the public railway infrastructure and their practical testing in the corresponding pilot project on one of the railway lines in Ukraine. According to the research results: 1) the necessary structure of the access regulation of private train locomotives to the public railway infrastructure was determined; 2) a logical order for interpreting the interaction between the relevant units of the owner (operator) of the public railway infrastructure and locomotive traction operators (owners of private locomotives) has been created.